FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI - Mariza Elvira; Novi Anggraini (Universitas Baiturrahim, 2019)
Hypertension is a condition when blood pressure increases chronically. Ministry of Health (2007) states, mortality due to hypertension ranks second of total deaths from non-communicable diseases (12.3%). The purpose of this study was to determine the factors associated with the incidence of hypertension in polyclinic disease in RSUD Dr. Achmad Mochtar Bukittinggi. This study used descriptive analytic method with cross sectional study approach with 100 respondents and using correlation dynamics technique, research instrument is questionnaire by using chi-square statistic test. The result of the study (46%) had age 35-55 years old (51%) had bad diet, (51%) had high stress and 51% respondents consumed cigarettes. The result of statistic test was found on the association of age factor with the incidence of hypertension p-value 0.031, on the association of dietary factors with the incidence of hypertension obtained p-value 0.083, on the relationship of stress factor with hypertension occurrence obtained p-value 0.050 and on the relationship of smoking factor to the incidence Hypertension was obtained p-value 0.204, so it can be concluded from the four factors, only the age factor and stress factors that are related to the incidence of hypertension. It is expected that the health service can conduct an extension activity about hypertension which will be used as routine hospital program in improving health degree